Knowledge transfer in on-collocated software architecture development: From the perspective of analysts and software architects - A., Salfarina; A. J., Marzanah; A., Sazly (2012)
Learning within software development involves the transfer of knowledge between different yet interdependent functional teams.In reality however, these teams often create islands of knowledge due mostly to indistinct flow of knowledge transfer (KT), thus fail to take advantage of the opportunity to learn from each other.Taking the non"collocated software architecture development teams as a challenge, the goal of this study is to investigate the nature of KT that occurs between the analyst and software architect teams in non-collocated software architecture development.Data are collected from semi"structured interviews with 30 respondents consisting of industrial experts ranging from analyst, software architects and project managers.We managed to gather sufficient evidence that proves KT occurs, and successfully characterize the areas of knowledge used and exchanged, the interdependency between teams, the utilization of knowledge, the medium used for KT and finally, the external conditions surrounding KT during non" collocated software architecture development.These findings are useful as they rest a good understanding of KT and its vital elements in non-collocated software architecture development for all prospective researchers and practitioners.